Pengaruh Brand Image terhadap Loyalitas Pelanggan terhadap Keputusan Pembelian Spring Automotif - Zainul Arifudin; Sugiharto Sugiharto; Harsono Teguh Santoso; Bambang Karnain; Achmad Daengs GS (Jurnal Mahasiswa Manajemen dan Akuntansi, 2025)
This study aims to determine the relationship between brand, quality, and price on customer loyalty. This study assesses the influence of brand variables (X1), quality (X2), and price (X3) on customer loyalty (Y). Data were collected through a questionnaire method with a quantitative approach. The research sample consisted of several respondents, namely product users, the general public who are familiar with the product, and employees of PT. Indospring, Tbk. Data collection was carried out to obtain relevant information regarding perceptions and attitudes towards brand, quality, price, and customer loyalty. Validity and reliability tests were conducted to ensure the accuracy and consistency of the data used in this study. As the main analysis, the multiple linear regression method was used to test the relationship between the independent variables (brand, quality, and price) with the dependent variable (customer loyalty). The SPSS program was used to perform statistical calculations and test the proposed hypotheses. The results of this study are expected to provide deeper insight into the factors that influence customer loyalty in the context of manufacturing companies, as well as provide recommendations for companies to improve marketing strategies and retain loyal customers.